Calcium-dependent and calcium-mimicking pathways regulate lead-induced myometrial contraction in water buffaloes - NAKADE, UDAYRAJ P; SHARMA, ABHISHEK; CHOUDHURY, SOUMEN; BHATIYA, SHIRISH; NAIR, SOORAJ V; SHARMA, VIPIN; YADAV, RAJKUMAR SINGH; GARG, SATISH KUMAR (The Indian Journal of Animal Sciences, 2017)
Lead produced dose-dependent contractile effect on buffalo myometrium and it was more marked on tonicity and amplitude while almost negligible on phasic contractions and frequency. In the presence of Ca2+-free Ringer Locke solution (RLS) and nifedipine, lead-induced uterotonic effect was significantly attenuated with decrease in Emax thus, suggesting major role of extracellular Ca2+ in uterotonic effect of lead and involvement of L-type Ca2+-channels in mediating this response. Direct excitatory effect of cyclopiazonic acid (CPA) on myometrium indicates possible Ca2+-influx via store operated calcium channels (SOCC). Lead failed to evoke any excitatory effect in the concurrent presence of nifedipine (1μM) and CPA (10μM), thus intracellular calcium seems to have negligible role in lead-induced myometrial contraction. In Ca2+-free high K+ (80 mM) depolarizing solution, lead-induced excitatory effect was attenuated by GF 109203X; which suggests permeation of lead through L-type Ca2+ channels to replace Ca2+ which directly activates protein kinase C (PKC) to produce excitatory effect. Thus lead seems to interact with calcium in buffalo myometrium in a dynamic fashion and exerts calcium-depending and calcium-mimicking effects; and therefore, lead is likely to have adverse effect on reproductive functions in buffaloes.